Focal Seizures in Patients With SCN1A Mutations: Response to Treatment. (February 2017) - McDonald, Christopher L.; Saneto, Russell P.; Carmant, Lionel; Sotero de Menezes, Márcio A.
The SCN1A gene has been implicated in the etiology of various forms of epilepsy. New research has linked this gene to specific types of epilepsy, all of which present in infancy or early childhood. This study examines the time course and pathology of pediatric patients who have a mutation in the SCN1A gene in order to open a discussion regarding the key trends of this form of epilepsy as well as important clinical considerations in management for patients who present with symptoms relating to the SCN1A mutations. We retrospectively examined 20 patients who presented to the clinic with focal seizures, as well as were positive for an SCN1A genetic mutation. Despite the small sample size, we were able to find important trends in the time course of the disorder as well as important areas of clinical practice that must be taken into consideration for these patients.